STRATEGI KOMUNIKASI PENGHAYAT KEPERCAYAAN SAPTA DARMA DALAM MEMPERTAHANKAN EKSISTENSI - Fajar Perdana Riski (LPSDI Bina Patria, 2022)
This study aims to determine the communication strategy of Sapta Darma Believers in maintaining their existence in Legowo Hamlet, Duren Village, Bandungan District, and Semarang Regency in terms of message planning, communication approach, and media selection. The theory used is the theory of symbolic interaction by George Harbert Mead. Interpretive phenomenological analysis was used in this study as a data analysis technique. The results of this study indicate that the strategy of Sapta Darma's Believers in Legowo Hamlet, Duren Village, Bandungan District, and Semarang Regency in maintaining existence is by implementing the concepts contained in the symbolic interaction theory in the form of Mind, Self-Concept, and Society. Deliberations with local government officials, religious leaders and the surrounding community are carried out as an effort to plan messages. The communication approach is carried out by staying in touch with other religious leaders, the local community and being involved in social activities. Finally, in the selection of media, Sapta Darma Believers use social media such as Facebook, Instagram. In addition, there is also a website that is managed by the administrator of the Sapta Darma center in Yogyakarta.